2018
DOI: 10.1071/bt18114
|View full text |Cite
|
Sign up to set email alerts
|

Trait variation of a generalist tree species (Eremanthus erythropappus, Asteraceae) in two adjacent mountain habitats: savanna and cloud forest

Abstract: Cloud forests and savannas differ in several environmental aspects, particularly in light irradiance and water availability. Such differences can be selective for specific sets of leaves and architectural strategies to capture light and use water. In the present study we evaluated functional traits variation in a generalist species in two adjacent habitats experiencing an abrupt change in resource availability (light and water availability). We collected several leaf, stem and architectural traits of the tree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 46 publications
1
5
1
Order By: Relevance
“…Studies of morphological variation into areas with different luminosity conditions showed such similarity to the traits found in our study when considering species with great adaptability (Borges et al 2019, Krupek & Lima 2012, Silva et al 2019. In this sense, the adaptative variations of Myrcia splendens allow its occurrence in different vegetation types, since the individual is able to explore new niches with efficiency (Amorim & Melo Júnior 2016).…”
Section: Discussionsupporting
confidence: 82%
“…Studies of morphological variation into areas with different luminosity conditions showed such similarity to the traits found in our study when considering species with great adaptability (Borges et al 2019, Krupek & Lima 2012, Silva et al 2019. In this sense, the adaptative variations of Myrcia splendens allow its occurrence in different vegetation types, since the individual is able to explore new niches with efficiency (Amorim & Melo Júnior 2016).…”
Section: Discussionsupporting
confidence: 82%
“…All functional data were obtained from data compilation for each species (Martins & Batalha 2006, Cianciaruso et al 2012, Prado-Junior et al 2016, except for crown length ratio that was measured during our sampling. Crown length ratio was measured as the ratio between the height of lower foliage and the height of each individual sapling surrounding the large tree (Borges et al 2018).…”
Section: Neighborhood Structure and Species And Functional Diversitymentioning
confidence: 99%
“…Trees display different ecological strategies in response to contrasting habitats under distinct environmental stresses (Borges et al 2019). Ecological strategies are expressed as a balance between functional traits and the environment, driven by environmental constraints, which may favour different sets of traits (Wright et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Functional traits are morpho-physiological-phenological characteristics that directly or indirectly affect plant performance through their effects on growth, survival, and reproduction (Violle et al 2007). Such adaptations are essential for the survival and expansion of species ecological limits (Ghalambor et al 2007), and are governed by modi cations in leaf traits, which enable species to overcome different environmental lters (Borges et al 2019), particularly associated with resource availability, such as water, nutrients, and light (Wellstein et al 2017). The coordinated relationship between functional traits can be expressed in a gradient of strategies that ranges from fast acquisition to e cient resource conservation (Wright et al 2004;Reich 2014).…”
Section: Introductionmentioning
confidence: 99%